Saúde mental nas universidades brasileiras: revisão integrativa e posterior sistemática sobre a frequência de transtornos mentais em estudantes universitários - Carvalho, Reinaldo Antonio De [UNIFESP] (2020)
This work aims to analyze Brazilian publications on mental disorders among university students. For this study, an integrative literature review was initially carried out with a search in the Virtual Health Library Portal, from 2009 to 2019, based on the following descriptors and the respective Boolean terms: "Academics" OR "Students" OR "University Students" OR "Mental Disorders" OR "Psychopathology" OR "Mental Health". The inclusion criteria were empirical articles in which at least one of the descriptors was present in the titles, abstracts and keywords. Studies with a disparate public to the university public or bibliographical reviews, theoretical essays, theses or dissertations were excluded. After applying the search criteria, 1,628 articles were identified and after screening and eligibility criteria, 60 studies were included for analysis. The highest prevalence found was Dependence on Psychoactive Substances (43 to 89%), Stress (50 to 75%), Common Mental Disorders (26 to 55%) and Depression (12 to 43%). Most publications were with medical (n=20) and nursing (n=17) students, carried out in southeastern Brazil (n=22). Subsequently, a deepening of the findings was performed through a systematic review of the literature. Since in both studies the prevalence found in university students was higher than in the general population, it is urgent that health care policies be developed considering the needs of this specific public.